Playing with feelings : video games and affect - Anable, Aubrey (University of Minnesota Press, 2018)
"How gaming intersects with systems like history, bodies, and code Why do we so compulsively play video games? Might it have something to do with how gaming affects our emotions? In Playing with Feelings, scholar Aubrey Anable applies affect theory to game studies, arguing that video games let us "rehearse" feelings, states, and emotions that give new tones and textures to our everyday lives and interactions with digital devices. Rather than thinking about video games as an escape from reality, Anable demonstrates how video games--their narratives, aesthetics, and histories--have been intimately tied to our emotional landscape since the emergence of digital computers. Looking at a wide variety of video games--including mobile games, indie games, art games, and games that have been traditionally neglected by academia--Anable expands our understanding of the ways in which these games and game studies can participate in feminist and queer interventions in digital media culture. She gives a new account of the touchscreen and intimacy with our mobile devices, asking what it means to touch and be touched by a game. She also examines how games played casually throughout the day create meaningful interludes that give us new ways of relating to work in our lives. And Anable reflects on how games allow us to feel differently about what it means to fail. Playing with Feelings offers provocative arguments for why video games should be seen as the most significant art form of the twenty-first century and gives the humanities passionate, incisive, and daring arguments for why games matter."--Publisher's description